Cambridge advanced learner's dictionary (Cambridge University Press, 2003)
The Cambridge Advanced Learner's Dictionary doesn't just help you find words quickly and understand them easily. It gives the vital support which advanced students need, especially with the essential skills: reading, writing, listening and speaking.